Graphene Oxide Immobilized Copper(II) Schiff Base Complex [GO@AF‐SB‐Cu]: A Versatile Catalyst for Chan‐Lam Coupling Reaction. Issue 4 (25th January 2019) - Kumar, Akash; Layek, Samaresh; Agrahari, Bhumika; Kujur, Shelly; Pathak, Devendra Deo
Abstract: Graphene oxide immobilized Cu(II) Schiff base complex, GO@AF‐SB−Cu, was synthesized by the reaction of a Schiff base functionalized Graphene oxide, GO@AF‐SB, with Cu(OAc)2 .H2 O in ethanol under reflux. The immobilized complex was isolated as a black‐coloured solid and characterized by various physico‐chemical techniques, such as Fourier transform infrared spectroscopy (FT‐IR), Fourier transform Raman spectroscopy (FT‐Raman), Powder X‐ray diffraction (PXRD), X‐ray photoelectron spectroscopy (XPS), Field emission scanning electron microscopy (FESEM), Energy dispersive X‐ray microscopy (EDX), Elemental mapping, Inductively coupled plasma atomic emission spectroscopy (ICP‐AES) and Thermo gravimetric analysis (TGA). The catalytic activity of the complex was explored in Chan‐Lam coupling reaction of amines and arylboronic acids without using any co‐catalyst or oxidant. Further, the catalyst could be easily recovered quantitatively from the reaction mixture by simple filtration and reused up to five times without significant loss in the catalytic activity. All the isolated organic products were characterized by 1 H and 13 C NMR spectroscopy. Abstract : Graphene oxide immobilized Cu(II) Schiff base complex, GO@AF‐SB−Cu was synthesized by the reaction of a Schiff base functionalized Graphene oxide, GO@AF‐SB with Cu(OAc)2 .H2 O in ethanol under reflux and characterized by various spectroscopic techniques. The catalytic activity of the complex was demonstrated in Chan‐Lam coupling reaction as a heterogeneous catalyst. Various aromatic, aliphatic and heterocyclic amines were investigated for this protocol. The catalyst could be easily recovered from the reaction mixture and reused up to five times.